1992
DOI: 10.3109/08958379209145317
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene: A Respiratory Tract Toxicant and Carcinogen for Mice

Abstract: The toxicologic and carcinogenic potential of naphthalene was studied by exposing groups of male and female B 6 U F , mice to atmospheres containing 0 (7.5 mice per sex), 70 ppm (7.5 mice per sex), or 30 ppm (150 mice per sex) of the chemical for 6 h daily, 5 dayslwk for 703 wk. The final mean body weights of mice exposed to naphthalene were similar to those of the controls. The survival of control male mice was significantly lower than that of the exposed males. The lower survival was attributed to wound trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 24 publications
4
48
0
Order By: Relevance
“…More recently, the toxicology database on naphthalene was substantially expanded through the publication of chronic toxicity/carcinogenicity studies in mice and rats in which naphthalene was administered by inhalation (Abdo et al 1992, Adkins et al 1986, NTP 1992, 2000. Of particular importance were the statistically significant increases in incidence of pulmonary alveolar/bronchiolar adenomas in female mice and nasal tumors in rats.…”
Section: Naphthalenementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the toxicology database on naphthalene was substantially expanded through the publication of chronic toxicity/carcinogenicity studies in mice and rats in which naphthalene was administered by inhalation (Abdo et al 1992, Adkins et al 1986, NTP 1992, 2000. Of particular importance were the statistically significant increases in incidence of pulmonary alveolar/bronchiolar adenomas in female mice and nasal tumors in rats.…”
Section: Naphthalenementioning
confidence: 99%
“…Genetic toxicity studies have mostly been negative (Schreiner et al 1989), although one C9 isomer was reported as mutagenic when tested under in vitro conditions (Janik-Spiechowicz et al 1998a, 1998b. In carcinogenicity studies, cumene, naphthalene, and methylnaphthalene isomers have produced respiratory tract tumors in rodents (Abdo et al 1992, NTP 1992, 2000, Murata et al 1993. Cumene, naphthalene, and other structurally similar aromatic chemicals (e.g., ethylbenzene, styrene) that cause similar tumor profiles in rodents are usually inactive in standard mutagenicity assays.…”
Section: Aromatic Solvents (C9-c12)mentioning
confidence: 99%
“…There is limited evidence in experimental animals for the carcinogenicity of anthanthrene, benz There is inadequate evidence in experimental animals for the carcinogenicity of acenaphthene, acepyrene (3,4-dihydrocyclopenta[cd] The NTP has investigated the carcinogenicity of NAP in both rats and mice, following inhalational exposure (Abdo et al, 1992). …”
Section: Pyrene (Ip) and (5-mch)mentioning
confidence: 99%
“…As discussed by North et al (2008), these bioassays found increased incidences of nasal respiratory epithelial adenomas and of rare nasal olfactory epithelial neuroblastomas in female rats, and of nasal respiratory epithelial adenomas in male rats exposed to naphthalene vapor concentrations of 10, 30, or 60 ppm for 2 years (NTP, 2000;Abdo et al, 2001;Long et al, 2003). There were increased incidences of alveolar/bronchiolar adenomas or carcinoma in female (but not male) B6C3F1 mice exposed to 30 (but not to 10) ppm naphthalene for 2 years (NTP, 1992;Abdo et al, 1992). A previous study found increased tumor multiplicity in tumor-bearing A/J strain mice exposed to 10 or 30 ppm for 6 months (Adkins et al, 1986).…”
Section: Introductionmentioning
confidence: 99%